1991
DOI: 10.1038/jcbfm.1991.105
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinins (Substance P, Neurokinin A, Neuropeptide K, and Neurokinin B) in the Cerebral Circulation: Vasomotor Responses in vitro and in situ

Abstract: Summary:The vasomotor responses of tachykinins have been studied in the cerebral vasculature of human, pig, cat, and guinea pig, Substance P (SP), neurokinin A (NKA), neurokinin B (NKB), and neuropeptide K (NPK) induced concentration-dependent relaxations of pre con tracted cerebral arteries in all species when examined by a sensitive in vitro technique, In addition, the relaxant responses to SP, NKA, and NKB were studied in cat pial arterioles by peptide microapplication in situ. In human pial vessels, the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 31 publications
3
36
2
1
Order By: Relevance
“…This, however, contrasts with the finding (Jansen et al, 1991) that in cat pial arteries, neurokinin A (0.01-1 JAM), a high affinity NK2 receptor agonist produced only dilatation. This apparent anomaly may suggest that species differences exist but seems more likely to reflect the poor selectivity of neurokinin A for NK2 receptors (Guard & Watson, 1991).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This, however, contrasts with the finding (Jansen et al, 1991) that in cat pial arteries, neurokinin A (0.01-1 JAM), a high affinity NK2 receptor agonist produced only dilatation. This apparent anomaly may suggest that species differences exist but seems more likely to reflect the poor selectivity of neurokinin A for NK2 receptors (Guard & Watson, 1991).…”
Section: Discussioncontrasting
confidence: 54%
“…In the present study, substance P markedly dilated guinea-pig pial arteries when injected perivascularly, an effect consistent with its vasodilator activity in a variety of species, both in vitro and in situ (Regoli et al, 1989;Jansen et al, 1991;Stubbs et al, 1992). Moreover, the potency with which substance P increased pial artery diameter in the guinea-pig was similar to that observed in cat cerebral vessels (Edvinsson et al, 1981;Jansen et al, 1991). Such a vasodilatation could activate trigeminal nerve endings and via the initiation of local axon reflexes lead to the sensation of pain (Humphrey & Feniuk, 1991).…”
Section: Discussionmentioning
confidence: 64%
“…The same stimuli probably also release substance P (Edvinsson et al, 1983) that is stored in a smaller proportion of dural nerve fibres (von During et al, 1990;Messlinger et al, 1993) where it may largely be co-localized with CGRP (O'Connor & van der Kooy, 1988), possibly in the same vesicles (Gulbenkian et al, 1986). Substance P has been shown in different species (man, guinea-pig, cat) to act as a powerful vasodilator on isolated intracranial arteries including the middle meningeal artery in vitro (Jansen et al, 1991;1992) and on cerebral arterioles of the cat in situ (Jansen et al, 1991). In our preparation, however, recent experiments have revealed that meningeal blood flow is not significantly changed by topical administration of substance P and the substance P analogue septide at concentrations of up to 10-3 M (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…of all nerve cell bodies contain CGRP and CGRP mRNA [50,187]. CGRP and SP are potent vasodilators in vivo and in vitro, the former being 10-1000 times more potent [45,58,59,106,136]. Several studies have suggested that SP is involved in plasma extravasation from postcapillary venules in the dura mater during primary headache attacks [131].…”
Section: Sensory Nervous Systemmentioning
confidence: 99%
“…δ-preprotachykinin produces SP only, whereas proteolytic cleavage of β-and δ-preprotachykinin produces SP [59,106] and a second tachykinin neurokinin A (NKA). The cerebrovascular distribution of NKA resembles that of SP and coexistence of SP and NKA in cell bodies of sensory ganglia and in perivascular nerve fibers have been demonstrated [31,41].…”
Section: Sensory Nervous Systemmentioning
confidence: 99%